PENELUSURAN TRANSFORMASI BENTUK ARSITEKTUR TRADISIONAL RUMAH ADAT KARAMPUANG - Meldawati Meldawati; Lottong Lottong (Universitas Fajar, 2016)
Changes in lifestyle, culture, religion, climate change and natural disasters because traditional homes are considered no longer able to accommodate the needs of its inhabitants. Karampuang customs area is the name of a village located +35 kilometers west of the district capital Sinjai South Sulawesi Indonesia, which has a history of birth